Poor knowledge of anemia and sexually transmitted disease but better knowledge of HIV/AIDS among unmarried adolescents aged 15-24 years - Sahiratmadja, Edhyana; Raharja, Mugia Bayu; Setiawati, Elsa Pudji; Panigoro, Ramdan (Faculty of Medicine, Universitas Trisakti, 2021)
BACKGROUND Basic knowledge of sexual and reproductive health is important to be introduced during the premarital period, to reduce high-risk sexual behavior among adolescents, as well as to increase the correct attitude in their future marriage. This study explored the knowledge of HIV/AIDS, sexually transmitted diseases (STDs) and anemia among unmarried adolescents. METHODS This was a cross-sectional analytical study on secondary data from the Indonesian Demographic and Health Population Survey 2017, initially conducted by the National Population and Family Planning Board (BKKBN). Knowledge of HIV/AIDS, STDs and anemia among unmarried adolescents aged 15-24 years in West Java Province and Jakarta, the capital city of Indonesia, was compared and analyzed using the chi-square test. RESULTS In total, 5,389 weighted data were retrieved. In general, adolescents in Jakarta had better knowledge of all diseases compared to those in West Java (p<0.001). Knowledge of anemia and STDs was poor compared to that of HIV/AIDS which was moderate to good (p<0.001). Interestingly, although the adolescents had a middle-low wealth index (43%), the majority (>90%) had their own mobile phone with almost daily internet access, however most of their information sources on health education were from their school period. CONCLUSION Premarital education in schools is imperative to enhance the knowledge of STDs and anemia. Moreover, poor knowledge of anemia is a challenge for introducing the topic of thalassemia major, an inherited autosomal recessive type of anemia due to hemoglobinopathy. Since Indonesia is harboring 6-10% of thalassemia carriers, integrative premarital education is needed for better family planning.